THE ASSOCIATION BETWEEN EXCLUSIVE BREASTFEEDING, MATERNAL NUTRITIONAL STATUS, MATERNAL ZINC INTAKE, AND STUNTING IN INFANTS AGED 6 MONTHS - Anindya, Ivanda Glanny; Salimo, Harsono; Dewi, Yulia Lanti Retno (Journal of Maternal and Child Health, 2020)
Background: Stunting is a form of malnutrition that has an impact on decreased learning achievement, motor and mental development and intellectual. Exclusive breastfeeding is a perfect nutrition for the First 1,000 Days of Life for normal growth. Maternal nutritional status also plays an important role for the success of breastfeeding whose indicators are measured by the duration of exclusive breastfeeding and the nutritional status of children. Adequacy of zinc is an important micronutrient during the child's growth period to prevent growth failure. This study aimed to analyze the association between exclusive breastfeeding, maternal nutritional status, maternal zinc intake, and stunting in infants aged 6 months.Subjects and Method: This was cross sectional study conducted in the 3 areas of Community Health Center, Jember Regency. The subjects of the study were infants aged 6 month and 115 mothers. Infants were selected by cluster sampling and simple random sampling for each area. The zinc intake data was obtained by the 24 hours Recall. Body Mass Index was used to obtain maternal nutritional status data. The stunting data measured by microtoise. The other data were collected by questionnaire. The data were analyzed by path analysis.Results: Exclusive breastfeeding (b = - 0.61; 95% CI = -1.42 to 0.21; p = 0.143) and maternal zinc intake (b = -0.04; 95% CI = 1.35 to 0.58; p = 0.436) directly decreased the risk of stunting in infants. Maternal BMI indirectly affected the risk of stunting in infants through exclusive breastfeedingConclusion: Exclusive breastfeeding and maternal zinc intake directly decrease the risk of stunting in infants. Maternal BMI (Body Mass Index) indirectly affect to the risk of stunting in infants through exclusive breastfeeding.Keywords:  Exclusive breastfeeding, nutritional status, zinc intake, stuntingCorrespondence: Ivanda Glanny Anindya. Masters Program in Nutrition, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: ivandaaglanny@gmail.com. Mobile: +6289648856374.Journal of Maternal and Child Health (2020), 5(1): 37-49https://doi.org/10.26911/thejmch.2020.05.01.05